Risk factors associated with anabolic-androgenic steroid use among adolescents - Bahrke, M. S.; Yesalis, C. E.; Kopstein, A. N.; Stephens, J. A. (Sports Medicine, 2000)
To identify risk factors associated with anabolic-androgenic steroid (AAS) use among adolescents, computerised and manual literature searches were performed and the resultant local, state, national and international reports of illicit AAS use by adolescents that referenced risk factors were reviewed. Results indicate that adolescent AAS users are significantly more likely to be males and to use other illicit drugs, alcohol and tobacco. Student athletes are also more likely than non-athletes to use AAS, and football players, wrestlers, weightlifters and bodybuilders have significantly higher prevalence rates than students not engaged in these activities. Currently, only a partial profile can be created to characterise the adolescent AAS user. Further research will be needed before associations can be made with a reasonable degree of confidence regarding risk factors such as athletic participation, ethnicity, socioeconomic status and educational level. More importantly, to improve prevention and intervention strategies, a better understanding of the process involved in initiating AAS use is needed, including vulnerability factors, age of initiation and the use of other illicit drugs.